Controlled viscoelastic particle encapsulation in microfluidic devices. Issue 35 (23rd August 2021) - Shahrivar, Keshvad; Del Giudice, Francesco
Abstract : We provide the first experimental evidence of viscoelastic particle encapsulation with single-particle encapsulation efficiency up to 2-fold larger than the stochastic value. Abstract : The encapsulation of particles in droplets using microfluidic devices finds application across several fields ranging from biomedical engineering to materials science. The encapsulation process, however, is often affected by poor single encapsulation efficiency, quantified by the Poisson statistics, with droplets containing more than one particle or with several empty droplets. We here demonstrate that viscoelastic aqueous solutions of xanthan gum enable controlled single particle encapsulation in microfluidic devices with a single encapsulation efficiency up to 2-fold larger than the one predicted by the Poisson statistics. We achieved such a result by identifying viscoelastic xanthan gum aqueous solutions that could drive particle ordering before approaching the encapsulation area and simultaneously form uniform droplets. This is the first experimental evidence of viscoelastic encapsulation in microfluidic devices, the existing literature on the subject being focused on Newtonian suspending liquids. We first studied the process of viscoelastic droplet formation, and found that the droplet length normalised by the channel diameter scaled as predicted for Newtonian solutions. At variance with Newtonian solutions, we observed that the droplet formation mechanism became unstable above critical values of the Weissenberg number, which quantifies the elasticity of the xanthan gum solutions carrying the particles. In terms of controlled encapsulation, we discovered that the single encapsulation efficiency was larger than the Poisson values in a specific range of xanthan gum mass concentrations. Finally, we introduced an empirical formula that can help the design of controlled viscoelastic encapsulation systems.